Challenges and advances for the treatment of renal cancer patients with brain metastases: From immunological background to upcoming clinical evidence on immune-checkpoint inhibitors. (July 2021) - Incorvaia, Lorena; Madonia, Giorgio; Corsini, Lidia Rita; Cucinella, Alessandra; Brando, Chiara; Gagliardo, Cesare; Santoni, Matteo; Fanale, Daniele; Inno, Alessandro; Fazio, Ivan; Foti, Giovanni; Galia, Massimo; et al.
Graphical abstract: Highlights: Brain metastases are specific site of interest representing a predictive factor of poor prognosis. Patients with BM were usually excluded from prospective clinical trials in the past. Recent data from pivotal trials suggest efficacy and safety of ICIs in BMs from RCC. The immunotherapy responsiveness seems to be complex and multifactorial. The genetic intratumor heterogeneity and the immunosuppressive TME are challenging. Abstract: The introduction of checkpoint inhibitors (ICIs) in renal cell carcinoma (RCC) treatment landscape, resulted in improvements in overall survival (OS) in metastatic patients. Brain metastases (BMs) are a specific metastatic site of interest representing a predictive factor of poor prognosis. Patients with BMs were usually excluded from prospective clinical trials in the past. Despite recent evidence suggest the efficacy and safety of ICIs, the BMs treatment remains a challenge; the immunotherapy responsiveness seems to be multifactorial and dependent on several factors, such as the genetic intratumor heterogeneity and the immunosuppressive role of the brain tumor microenvironment. This review, starting from the immunological background in RCC BMs, provide an overview of the upcoming evidence from clinical trials, address the issues related to the neuroradiological immunotherapy response evaluation and, with a look to the future, describes how the epigenetic modulation of immune evasion could represent a background for new therapeutic strategies.